Radar-Based Invisible Biometric Authentication - Maria Louro da Silva; Carolina Gouveia; Daniel Filipe Albuquerque; Hugo Plácido da Silva (Information, 2024)
Bio-Radar (BR) systems have shown great promise for biometric applications. Conventional methods can be forged, or fooled. Even alternative methods intrinsic to the user, such as the Electrocardiogram (ECG), present drawbacks as they require contact with the sensor. Therefore, research has turned towards alternative methods, such as the BR. In this work, a BR dataset with 20 subjects exposed to different emotion-eliciting stimuli (happiness, fearfulness, and neutrality) in different dates was explored. The spectral distributions of the BR signal were studied as the biometric template. Furthermore, this study included the analysis of respiratory and cardiac signals separately, as well as their fusion. The main test devised was authentication, where a system seeks to validate an individual’s claimed identity. With this test, it was possible to infer the feasibility of these type of systems, obtaining an Equal Error Rate (EER) of <semantics>3.48%</semantics> if the training and testing data are from the same day and within the same emotional stimuli. In addition, the time and emotion results dependency is fully analysed. Complementary tests such as sensitivity to the number of users were also performed. Overall, it was possible to achieve an evaluation and consideration of the potential of BR systems for biometrics.